Potential Therapeutic Benefits of Dipyridamole in COVID-19 Patients - Aliter, Kholoud F. (Curr Pharm Des, 2021)
BACKGROUND: COVID-19 pandemic is caused by coronavirus also known as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The viral infection continues to impact the globe with no vaccine to prevent the infection or highly effective therapeutics to treat the millions of infected people around the world. The disease starts as a respiratory infection, yet it may also be associated with a hypercoagulable state, severe inflammation owing to excessive cytokines production, and a potentially significant oxidative stress. The disease may progress to multiorgan failure and eventually death. OBJECTIVE: In this article, we summarize the potential of dipyridamole as an adjunct therapy for COVID-19. METHODS: We reviewed the literature describing the biological activities of dipyridamole in various settings of testing. Data were retrieved from PubMed, SciFinder-CAS, and Web of Science. The review concisely covered relevant studies starting from 1977. RESULTS: Dipyridamole is an approved antiplatelet drug, that has been used to prevent stroke, among other indications. Besides its antithrombotic activity, the literature indicates that dipyridamole also promotes a host of other biological activities including antiviral, anti-inflammatory, and antioxidant ones. CONCLUSION: Dipyridamole may substantially help improve the clinical outcomes of COVID-19 treatment. The pharmacokinetics profile of the drug is well established which makes it easier to design an appropriate therapeutic course. The drug is also generally safe, affordable, and available worldwide. Initial clinical trials have shown a substantial promise for dipyridamole in treating critically ill COVID-19 patients, yet larger randomized and controlled trials are needed to confirm this promise.